Effect of Yoga and Naturopathy on an Obese Male Patient: A Case Report - Nair, Jyoti; M, Sathya Joicy; .S, Logeshwaran (Indian Journal of Integrative Medicine, 2025)
Globally, the incidence of overweight and obesity continues to rise, raising concern about the health hazards that come with this growing issue. An increased number of chronic illnesses are associated with high Body Mass Index (BMI). The percentage of overweight or obese men and women was found to be 38.4% and 36.2%, respectively. A middle-aged man came to our hospital with the complaint of increase in weight and Blood pressure, showing altered in serum lipid profile. He underwent Yoga and Naturopathy treatments which include massage therapy, fasting and diet therapy, yoga therapy, and few more treatments. There was a considerable reduction in his weight in which pre -110 kg and post- 102.5 kg (loss of about 8 Kgs), BMI pre -39 Kg/ m2, post – 36.3 Kg/m2, Blood pressure pre 160/120, post 118/84 and further BP maintained without medication. In the Lipid profile LDL pre -138 mg/dl, post - 116 mg/dl, Total cholesterol pre- 203 mg/dl, post- 186 mg/dl and the associated symptoms of obesity like breathing difficulty, heaviness of body and difficulty in walking also improved. This case report recommends that Naturopathy and Yoga were found to be effective in managing obesity.